PUMPING TEST DATA ANALYSIS AND GROUNDWATER QUALITY OF WEST JAKARTA AND ITS SURROUNDING AREA - Lorensius Hutagaol, Reinhat
The research area is located is in three cities, i.e., West Jakarta City, Central Jakarta City, and North Jakarta City, with 184.452 km2 wide. Excessive groundwater exploitation often occurs in urban areas with rapid industrial growth. Common hydrogeological problems in areas with these conditions are land subsidence, groundwater contamination, and the occurrence of salt water in coastal area. The purposes of this research are to estimate the aquifer type and aquifer parameters values, evaluate groundwater quality, and analyze the relationship between geological settings at research area with aquifer parameters and its groundwater quality. The research area is divided into two geomorphological units, i.e., Coastal Plain Unit and Bogor Volcanic Fan Unit. Stratigraphically, the research area consists of two formations, Kaliwangu Formation that formed during Pliocene and Citalang Formation that formed during Pleistocene. These two formations are part of Jakarta Groundwater Basin and act as aquifers in the research area with of sandstone and claystone interbeds. Aquifer parameters determination was performed to 14 wells (Well 1 – Well 14), drilled in 2015 and analyzed with Jacob method. Meanwhile, groundwater quality analysis was performed to 19 groundwater samples which were taken in 2016. All wells are suspected of penetrating the aquifer zone at the Kaliwangu Formation. From the aquifer type determination, it is known that the research area consists of two aquifer types: confined aquifer and leaky aquifer. The estimation shows that aquifer transmissivity ranges from 2,33 x 10-5 – 5,2 x 10-4 m 2 /s. The total dissolved solids (TDS) of groundwater range from 368 to 2.948 mg/L, nitrate values range from 0 to 52,97 mg/L, and pH values range from 6,26 to 8,62. Groundwater facies at research area consists of NaCl type, NaHCO3 type, Ca(HCO3)2 type, and non-dominant type. Domination of chloride at the northern part of research area may be caused by groundwater evolution and seawater intrusion.